POSSIBLE PARENTERAL METHOTREXATE APPLICATION IN THE TREATMENT OF JUVENILE IDIOPATHIC ARTHRITIS - Yu. М. Spivakovsky; Yu. V. Chernenkov; А. Yu. Spivakovskaya; О. V. Skupova; Yu. K. Gerasimenko; Т. G. Sukhova (Вопросы современной педиатрии)
The article describes a case of using methotrexate for subcutaneous injection in a rated dose of 12.5 mg / m2 of body surface per week when treating a child with juvenile idiopathic arthritis. When switching to the parenteral route of administration, methotrexate ensured the development of joint syndrome remission, normalization of laboratory indices of disease activity, and improvement of joint functions. After 6 months the inactive disease stage was detected, and after 12 months — remission.